1995
DOI: 10.1105/tpc.7.8.1307
|View full text |Cite
|
Sign up to set email alerts
|

The maize Dwarf3 gene encodes a cytochrome P450-mediated early step in Gibberellin biosynthesis.

Abstract: Gibberellins (GAs) are phytohormones required for normal growth and development in higher plants. The Dwarf3 (03) gene of maize encodes an early step in the GA biosynthesis pathway. We transposon-tagged the 0 3 gene using Robertson's Mutator (Mu) and showed that the mutant allele d3-2::Mu8 is linked to a Mu8 element. The DNA flanking the Mu8 element was cloned and shown to be linked to the d3 locus by mapping in a high-resolution population developed by selecting for recombination between d3 and linked genetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
109
1

Year Published

1996
1996
2018
2018

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 209 publications
(112 citation statements)
references
References 42 publications
2
109
1
Order By: Relevance
“…The CBB3 protein might therefore act as a catalyst for a specific hydroxylation reaction in the biosynthesis of brassinosteroids. The recently isolated maize DWARF3 gene, coding for a cytochrome P450 enzyme involved in a hydroxylation step in gibberellin biosynthesis, provides an example of this type of activity (Winkler and Helentjaris, 1995). The data presented here, however, exclude an involvement of the CBB3 protein in the gibberellin biosynthetic pathway.…”
Section: Discussioncontrasting
confidence: 37%
“…The CBB3 protein might therefore act as a catalyst for a specific hydroxylation reaction in the biosynthesis of brassinosteroids. The recently isolated maize DWARF3 gene, coding for a cytochrome P450 enzyme involved in a hydroxylation step in gibberellin biosynthesis, provides an example of this type of activity (Winkler and Helentjaris, 1995). The data presented here, however, exclude an involvement of the CBB3 protein in the gibberellin biosynthetic pathway.…”
Section: Discussioncontrasting
confidence: 37%
“…AtBR6ox and its homologs form a family with CPD and DWF4, BR-related P450 genes, in a phylogenic tree. The only exception is the maize (Zea mays) Dwarf3 gene that was reported to be involved in gibberellin biosynthesis (Winkler and Helentjaris 1995). The present work demonstrated that AtBR6ox and tomato Dwarf are involved in C-6 oxidation, and hence the corresponding proteins were designated BR-6-oxidases.…”
Section: Discussionmentioning
confidence: 77%
“…2). An amino acid alignment of two CYP proteins involved in brassinosteroid biosynthesis (22␣-hydroxylase DWF4/CYP90B1 [Choe et al, 1998]; 23␣-hydroxylase CPD/CYP90A1 [Szekeres et al, 1996]) and other CYP proteins that are involved in gibberellin biosynthesis and dwarfism (DWF3/ CYP88A1 [Winkler and Helentjaris, 1995]; ROTUN-DIFOLIA/CYP90C1 [Kim et al, 1998]; and DWARF/ CYP85 [Bishop et al, 1996]) with CYP87A3 revealed highly conserved domains in these proteins in addition to the C-terminal heme-binding domain. All of these proteins exhibit a central region with steroid substrate-binding and oxygen-binding domains (Fig.…”
Section: Cyp87a3 Is Coding For a Protein That Belongs To The Cyp Supementioning
confidence: 99%